Copyrighting facts? Ownership of news images. Issue 1 (3rd July 2018) - Olson, Kathleen K.
ABSTRACT: Striking the proper balance between private intellectual property interests and the public interest is especially important in the context of news, given its fundamental role in democracy. This article examines the scope of copyright protection for photojournalism, as well as the First Amendment safeguards that may limit that protection. It focuses on current understandings of the fair use doctrine and the idea/expression dichotomy (and idea/expression merger.) Next it focuses on the federal district court ruling in the Zapruder film case, which was based on one of the fair use doctrine's key questions, but which also considered and rejected an idea/expression merger defense. An analysis of that case, and also a pair of key law review articles on copyright and images, leads to a proposal for a new "public-interest merger" doctrine for balancing public and rights holders' interests in cases involving news images. That proposal argues for focus on whether the news images are exclusive (or at least nearly so), and evidentiary.